Plasticizing and antiplasticizing effects of glycerol and sorbitol on biodegradable cassava starch films - Shimazu, Angélica Aimoto; Mali, Suzana; Grossmann, Maria Victória Eiras (Semina: Ciências Agrárias, 2007)
In this work were studied the plasticizing - antiplasticizing effects of glycerol and sorbitol on moisture sorption and mechanical properties of cassava starch films. Films were produced by casting with cassava starch (3g starch/100 g filmogenic solution) and different concentrations of glycerol or sorbitol (0, 5, 10, 15, 30 and 40 g/100 g starch). Glycerol and sorbitol acted as antiplasticizers when used at a low concentration (<span style="font-size: 8pt; color: #231f20; font-family: Verdana; mso-bidi-font-family: 'Times New Roman'; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">?15 g/100 g starch) and low values of water activity (<span style="font-size: 8pt; color: #231f20; font-family: Verdana; mso-bidi-font-family: 'Times New Roman'; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">?0,58). The antiplasticizing effect could be demonstrated by the decrease in hydrophilicity and in flexibility of the films at these conditions. At higher concentrations and higher water activity values, the employed plasticizers exerted its plasticizing effect.